Institucionalización del cuidado de enfermería a la gestante en chilpancingo, guerrero, méxico - Hernández Nava, Imelda Socorro (2016)
Introduction - the pregnant nursing care is governed by standard NOM-007-SSA2 - 2010. In Guerrero, 50% of pregnant women attend consultation during first quarter, concerned delay in contact with health services little correspondence between our services and expectations, objective - 1. Describe and analyze the established dynamic, instituting and institutionalization of nursing care to pregnant women. Qualitative, descriptive method in ten nurses, four medical and ten pregnant women in the third trimester selected by method not probabilistic convenience during prenatal consultation, interviewed in depth at his home, accepting to participate prior informed consent. Stage seven health centers, we used the analysis theme, considering ethical principles and criteria of strictness. Results: three categories; 1 care nursing instituted. Subcategories: 1.1.Care nursing routine according to official standard 1.2 Nursing Care Vertical Vs. Horizontal. 1.3.Nursing care as an exercise of power. Category 2: instituting nursing care received by the mother. 2.1 Subcategories (In) satisfaction of nursing care; 2.2. Practices Vs. daily incipient dialogue. 2.3 Dynamic Vs restrictive care holistic nursing.Category 3.Process institutionalization of care to pregnant women. Subcategories 3.1. Monitoring care facility in pregnant 3.2 Family involvement in the care of pregnant women Conclusion: Nurses comply with established, applying protocols and imposing the power structure of the institution. Care is more instrumental to that human, pregnant claim interest, good treatment, satisfaction with care and good communication.